Identification of challenges and their solution for smart supply chains in Industry 4.0 scenario: a neutrosophic DEMATEL approach. Issue 1 (6th September 2021) - Tripathi, Shubham; Gupta, Manish
Industry 4.0 has brought a new perspective to supply chains with latest technologies and connectivity to attain maximum outputs with minimum inputs and introduced a service oriented economy making supply chains smarter. A systematic transformation is crucial to ensure that organisations reap maximum benefits of the revolution. This study identifies key constraints causing hindrance in smooth transformation and analyses their influence among themselves and the entire system using a neutrosophic DEMATEL approach. A group of experts were consulted from academia and industry to formulate the final list of 13 challenges which include lack of standardisation, IPR concerns, data issues and lack of skilled workforce. The results will facilitate policy makers and managers to understand their significance and prioritisation. As addressing these barriers will expedite the transformation process, possible solutions to identified barriers are discussed to provide future direction on overcoming these challenges.